Mental health aspect of quality of life in the menopausal transition - Jelena Dotlic; Sanja Radovanovic; Biljana Rancic; Branislav Milosevic; Selmina Nicevic; Ilma Kurtagic; Nikolina Markovic; Tatjana Gazibara (Journal of Psychosomatic Obstetrics and Gynecology, 2021)
Purpose To evaluate factors associated with mental health quality of life (QOL), such as depressed mood, anxiety, poor memory and sleep, among midlife women according to the menopausal status. Material and methods Participants were 500 women aged 40–65 years. Data were collected using socio-demographic questionnaire, Women’s Health Questionnaire (domains of depressed mood-DEP, anxiety-ANX, memory-MEM and sleep-SLE) and Short Form-36 (Mental Composite Score) for assessment of health-related QOL. Factors associated with poorer DEP, ANX, MEM and SLE were examined using adjusted linear regression models. Results In premenopausal women, lower household monthly income (p = .046) was associated with higher level of DEP; higher body mass index (p = .045) was associated with higher ANX; having gynecological illnesses (p = .017) and menopause-related symptoms (p = .039) were associated with poorer MEM; being married (p = .036), drinking alcohol (p = .036) and having more physical activity (p = .041) was associated with better SLE. In postmenopausal women, worse DEP was more likely among women residing in city outskirts (p = .009), who are not married (p = .038) and with sedentary occupations (p = .049); lower education level (p = .030) was associated with more ANX; lower education level (p = .045) and having menopause-related symptoms (p = .044) were associated with poorer MEM; not engaging in regular recreation (p = .031) was associated with better SLE. Conclusions To improve QOL, pre- and postmenopausal women should not only be supported in the management of menopause-specific symptoms. Women should also receive recommendations as to the behavioral and personal changes when approaching the midlife period.